Effect of Feeding Rumensin during the growing phase on subsequent reproductive performance of yearling heifers - Corah, L.; Bolsen, K.; McKee, M.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Seventy five purebred heifers were used to determine whether Monensin, (trade name Rumensin) fed during the initial growing period after weaning, would affect the reproductive performance of yearling heifers. Rumensin had virtually no effect on reproductive performance as determined by the percentage of heifers cycling at the start of the breeding season or the percentage of heifers that conceived at first service and during the breeding season. A slightly higher percentage of the Rumensin fed heifers were cycling at the start of the breeding season. Although the study shows that replacement heifers on roughage rations can successfully be fed Rumensin, causing both a savings in feed as well as improved growth rate, current clearance of Rumensin does not recommend its use with breeding animals.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Growth; Reproductive performance; Yearling heifers